2019
DOI: 10.1210/en.2019-00314
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Signaling Drives Ciliogenesis in Human Endometrial Organoids

Abstract: The human endometrium is the inner lining of the uterus consisting of stromal and epithelial (secretory and ciliated) cells. It undergoes a hormonally regulated monthly cycle of growth, differentiation, and desquamation. However, how these cyclic changes control the balance between secretory and ciliated cells remains unclear. Here, we established endometrial organoids to investigate the estrogen (E2)-driven control of cell fate decisions in human endometrial epithelium. We demonstrate that they preserve the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 57 publications
4
66
1
Order By: Relevance
“…In addition, the proportion of ciliated cells significantly increased following the E2 treatment, which indicated that cilia were one of the indicators of epithelial cell differentiation. This was consistent with the study conducted by Haider et al., in which E2 signaling induced ciliogenesis in the endometrium and organoids [ 23 ]. Combining E2 stimulation and NOTCH pathway inhibition greatly increased the ciliogenesis.…”
Section: Eos Responsiveness To Hormonessupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, the proportion of ciliated cells significantly increased following the E2 treatment, which indicated that cilia were one of the indicators of epithelial cell differentiation. This was consistent with the study conducted by Haider et al., in which E2 signaling induced ciliogenesis in the endometrium and organoids [ 23 ]. Combining E2 stimulation and NOTCH pathway inhibition greatly increased the ciliogenesis.…”
Section: Eos Responsiveness To Hormonessupporting
confidence: 93%
“…The EOs culture medium usually contains ENRA, which means epidermal growth factor (EGF), Noggin, R-spondin-1, and A83–01. According to the discrepancies of experimental purposes and conditions, researchers would add different factors ( Table 1 ), such as WNT3A (for mouse EOs), fibroblast growth factor 10 (FGF10), hepatocyte growth factor (HGF), nicotinamide, p38 inhibitor SB202190, and glycogen synthase kinase 3β inhibitor CHIR99021 [ 18–20 , 23 ]. For mouse EOs, Boretto et al.…”
Section: The Components Of the Eos Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…Although recent studies have demonstrated that endometrial organoid cultures can be used to achieve the complexity of organ structures to a considerable degree through cellular self-assembly and can be used as preclinical models to study the physiology and pathology of human endometrium [17][18][19][20][21][22][23][24], these models do not fully recapitulate the regulatory mechanisms of endometrium in vivo. Herein with the use of full thickness endometrial tissue slice cultures we developed a unique model that dramatically enhances endometrial tissue viability and recapitulates the zone-specific changes seen in normal physiological conditions of endometrium [52][53][54].…”
Section: Induction Of Glandular Remodeling and Decidualization In Endmentioning
confidence: 99%
“…Recently, the development of 3D organoid cultures has gained attention as a powerful tool to study endometrial remodeling [17][18][19][20][21][22][23][24]. These cultures exploit the self-organization ability of endometrial cell types that reproduce many aspects of the phenotypical characteristics of endometrium [17][18][19][20][21][22][23][24]. The flexibility, reliability and reproducibility of organoid cultures derived from human endometrial cell types have largely helped to overcome the obstacle due to lack of animal models.…”
Section: Introductionmentioning
confidence: 99%